AB0380 The Inhibition of Tumor Necrosis Factor-Alpha (TNFA) Reduce Plasmatic Reactive Oxygen Metabolites (ROM) of Rheumatoid Arthritis (RA) Patients. (10th June 2014) - Cacciapaglia, F.; Anelli, M.G.; Rizzo, D.; Morelli, E.; Rotondo, C.; Rinaldi, A.; Covelli, M.; Iannone, F.; Lapadula, G.
Abstract : Background: Accumulating evidences indicate that chronic inflammation and oxidative stress play a key role in the early and accelerated atherosclerosis seen in patients with RA (1). Tumor necrosis factor-alpha (TNFa) overproduction is thought to be the main contributor to increased ROS release in patients with RA (2). TNFa inhibitors are effective treatments in the management of RA but the effects of these drugs on the heart and vessels is under investigation (3, 4). Objectives: The aim of this study was to assess the circulating levels of reactive oxygen metabolites (ROMs) during anti-TNFa treatment in RA. Methods: Forty patients with RA (36 female; age 53±13yrs) treated with different TNFa inhibitors were analyzed for 52 weeks. The oxidant status was determined from plasmatic samples taken before, 24 and 52 weeks after anti-TNFa treatment, by assessing hydroperoxides levels using a Diacron automated method (d-ROMs test), which has proved to be clinically useful as an oxidative stress marker (5). Results: Mean ROMs levels before TNFa-inhibitors were 33.2±10 mg H2O2/dL while after 24 and 52 weeks of treatment they were 29.5±7 and 29.3±9 mg H2O2/dL, respectively (P<0.05). Twenty-two (55%) RA patients with active disease had high d-ROM level (>32 mg H2O2/dL). After 24 and 52 weeks of anti-TNFa treatment 50% of patients reached remission/low disease status (DAS-28CRP<3.2) and all these patients had low d-ROM levels (<27 mg H2O2/dL). Conclusions: Our result demonstrate that good disease control with anti-TNFa agents is able to reduce oxidative stress in RA patients. References: Shoenfeld Y. et al. Circulation 2005;112:3337-47. Szekanecz Z. et al. Ann N Y Acad Sci 2007;1108:349-58. Cacciapaglia F. et al. Autoimmun Rev 2011;10(10):631-5. Kageyama Y. et al. Clin Exp Rheumatol. 2008;26(1):73-80. Vassalle C. et al. J Atheroscler Thromb 2012;19(8):712-7. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2556